Associations between Dietary Fiber and Colorectal Polyp Risk Differ by Polyp Type and Smoking Status. Issue 5 (26th February 2014) - Fu, Zhenming; Shrubsole, Martha J.; Smalley, Walter E.; Ness, Reid M.; Zheng, Wei
Abstract: The association of dietary fiber intake with colorectal cancer risk is established. However, the association may differ between cigarette smokers and nonsmokers. We evaluated this hypothesis in a large colonoscopy-based case-control study. Dietary fiber intakes were estimated by self-administered food frequency questionnaire. Unconditional logistic regression analysis was used to estimate ORs and 95% CIs with adjustment for potential confounders. Analysis also was stratified by cigarette smoking and sex. High dietary fiber intake was associated with reduced risk of colorectal polyps ( P- trend = 0.003). This association was found to be stronger among cigarette smokers ( P- trend = 0.006) than nonsmokers ( P -trend = 0.21), although the test for multiplicative interaction was not statistically significant ( P = 0.11). This pattern of association was more evident for high-risk adenomatous polyps (ADs), defined as advanced or multiple ADs ( P -interaction smoking and dietary fiber intake = 0.09). Among cigarette smokers who smoked ≥23 y, a 38% reduced risk of high-risk ADs was found to be associated with high intake of dietary fiber compared with those in the lowest quartile fiber intake group ( P- trend = 0.004). No inverse association with dietary fiber intake was observed for low-risk ADs, defined as single nonadvanced ADs. Cigarette smoking may modify the association of dietary fiber intake with the risk of colorectal polyps, especially high-risk ADs, a well-established precursor of colorectal cancer.